Revisiting the Creation Mandate 'Be Fruitful and Multiply, Fill the Earth and Subdue It' in Genesis 1:28 from an Ecotheological Perspective - Panggarra, Robi; Budiman, Sabda (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
The creation mandate that God gives to humanity is encapsulated in the phrase